2017
DOI: 10.1002/art.40054
|View full text |Cite
|
Sign up to set email alerts
|

Peficitinib, a JAK Inhibitor, in Combination With Limited Conventional Synthetic Disease‐Modifying Antirheumatic Drugs in the Treatment of Moderate‐to‐Severe Rheumatoid Arthritis

Abstract: In patients with moderate-to-severe RA, orally administered once-daily peficitinib in combination with limited csDMARDs resulted in a dose-dependent ACR20 response rate over 12 weeks with satisfactory tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
73
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 20 publications
5
73
2
1
Order By: Relevance
“…In contrast to the 2 previous phase IIb studies with peficitinib (13,15), no dose-dependent ACR20 response was observed, although analysis of the DAS28 and the inflammatory markers, CRP and ESR, did suggest a dose-dependent response in the overall population. In contrast to the 2 previous phase IIb studies with peficitinib (13,15), no dose-dependent ACR20 response was observed, although analysis of the DAS28 and the inflammatory markers, CRP and ESR, did suggest a dose-dependent response in the overall population.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…In contrast to the 2 previous phase IIb studies with peficitinib (13,15), no dose-dependent ACR20 response was observed, although analysis of the DAS28 and the inflammatory markers, CRP and ESR, did suggest a dose-dependent response in the overall population. In contrast to the 2 previous phase IIb studies with peficitinib (13,15), no dose-dependent ACR20 response was observed, although analysis of the DAS28 and the inflammatory markers, CRP and ESR, did suggest a dose-dependent response in the overall population.…”
Section: Discussioncontrasting
confidence: 95%
“…Only in Europe, where the placebo response rate was in the expected range, was there a statistically significant difference between any peficitinib group and placebo in the ACR20 response rate, which is consistent with previous peficitinib phase IIb studies (13,15). This response ALT rate was considerably higher than the assumed placebo response rate of 30% in the sample size calculation.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations